2017
DOI: 10.4269/ajtmh.17-0062
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Prevention Practices among U.S. Pregnant Immigrants from Zika Virus Outbreak Areas

Abstract: We administered an anonymous survey to assess knowledge, attitudes, and prevention practices related to the Zika virus among pregnant women residing in Texas. Multivariate logistic regression models controlling for age, race/ethnicity, education, and number of years in the United States assessed differences between women born in outbreak areas ( = 390) versus those born in the United States ( = 249). Results demonstrated that most women wanted more information on the Zika virus and desired to obtain it from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
28
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 7 publications
4
28
1
2
Order By: Relevance
“…These results are consistent with those from prior studies, which found low ZIKV knowledge across the United States and among Latinx participants [16,19,20]. Notably, they found low knowledge regarding sexual transmission and ZIKV prevention methods, such as preventing mosquito bites and using condoms during sex [15,21,22]. In our study, we had hypothesized that women who stand to benefit the most from ZIKV prevention (ie, pregnant) and those who are most frequently exposed to communications about ZIKV would have greater knowledge of its long-term consequences and how to manage ZIKV risk during pregnancy.…”
Section: Discussionsupporting
confidence: 91%
“…These results are consistent with those from prior studies, which found low ZIKV knowledge across the United States and among Latinx participants [16,19,20]. Notably, they found low knowledge regarding sexual transmission and ZIKV prevention methods, such as preventing mosquito bites and using condoms during sex [15,21,22]. In our study, we had hypothesized that women who stand to benefit the most from ZIKV prevention (ie, pregnant) and those who are most frequently exposed to communications about ZIKV would have greater knowledge of its long-term consequences and how to manage ZIKV risk during pregnancy.…”
Section: Discussionsupporting
confidence: 91%
“…Thus, there is a need for enforcement of physician role in this issue; particularly that physician office and clinics are the most accurate sources of information regarding medical problems. 30 Travelers are sentinels of ZIKAV transmission. 31 A positive association was found between the level of knowledge and travel history in Greece, 18 nevertheless, such association was not found in the sample population in United States.…”
Section: Discussionmentioning
confidence: 99%
“…This situation has led to misunderstanding of the risks involved in DEET usage and probably reduced its deployment as a protective measure for blocking arthropod transmission of pathogens. For instance, an anonymous survey of pregnant women in the southern United States was conducted during the Zika virus epidemic, and found that 50% of the pregnant women questioned would not use an insect repellent due to concerns about use during pregnancy . Yet, a randomized controlled trial conducted among 897 pregnant women who were given 1.7 g of DEET per night throughout the second and third trimesters resulted in no significant differences in birthweight, newborn anthropometrics, newborn neurologic exams, or developmental milestones in the first year of life between control and treatment groups .…”
Section: Introductionmentioning
confidence: 99%